Five Truths about Internationalization - Knight, Jane (International Higher Education, 2012)
University internationalization is evolving and becoming more complex. This article explores five key elements of internationalizationthe local context, "one size does not fit all," unintended consequences, internationalization is not an end in itself, and globalization and internationalization are linked, but not the same thing.